On the Nonlinearity of Extended s-Type Weighted Nakano Sequence Spaces of Fuzzy Functions with Some Applications - Awad A. Bakery; Elsayed A. E. Mohamed (Journal of Function Spaces)
We have defined and studied the weighted Nakano sequence spaces of fuzzy functions. We have constructed the ideal generated by extended s-fuzzy functions and the sequence spaces of fuzzy functions. We present some topological and geometric structures of this class of ideal and multiplication mappings acting on this sequence space of fuzzy functions. Moreover, the existence of Caristi’s fixed point is examined. To show how the work is done, some examples and applications to the existence of solutions for a class of nonlinear summable and matrix equations are also talked about.